Persepsi Mahasiswa Terhadap Pentingnya Perilaku Pro Sosial Di Jurusan Bimbingan Penyuluhan Islam - Nurhalizah, Nurhalizah Soleha; Suryani, Heni; Shobron, Ilmi Rani; Mardiyah, Ainul (IAINU Kebumen, 2025)
Prosocial behavior is defined as a voluntary action intended to help or benefit an individual or group of individuals. This study aims to analyze the perceptions of Islamic Guidance and Counseling Department students on the importance of prosocial attitudes in their academic and social lives. This study uses a qualitative approach with a case study method. The data collection technique was in-depth interviews with four BPI students at the State Islamic University of North Sumatra. The data were analyzed using thematic analysis to identify emerging patterns and themes. The results showed that the majority of Islamic Guidance and Counseling Department students had a positive perception of the importance of prosocial attitudes in their academic lives and in their roles as prospective mentors and counselors.